Challenges and impacts of the absence of public libraries in rural South Africa - Mashilo, Sedume; Mdhlalose, Dickson Scotch (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2025)
This study examines the adverse consequences of rural communal inaccessibility to a free public library. Making educated judgments to accomplish growth-oriented and educational objectives requires having access to accurate and pertinent information. Public libraries support the development of society and the economy by providing information necessary for informed engagement in societal activities, such as gaining entry to prospects. Fifty individuals were chosen using purposeful selection from various classifications in the rural areas of Kwa-Mhlanga, Mpumalanga, South Africa, as part of the study's qualitative research methodology. Discussion groups and organized interviews were used to gather data, which were subsequently subjected to thematic analysis. Rural communities around Kwa-Mhlanga have an acute requirement for a public library. The community's educational, socioeconomic, cultural, and economic prosperity is adversely impacted when education, knowledge, and supporting resources are unavailable. To satisfy the information demands of the many populations that comprise the town, the study suggests the creation of a public library that is adequately equipped, kept up to date, and constantly updated. The villages that encompass Kwa-Mhlanga should organize a community group to advocate for the opening of a public library or library facility, work with nearby schools to enhance library materials and promote community utilization after class hours, and work with neighbourhood organizations to set up a mobile library that delivers books and resources to different parts of the community.